C is correct

S=(a+b*)*=(a*(b*)*)*=(a*b*)*

T=(a+b)*=(a*b*)* so S=T

S=(a+b*)*=(a*(b*)*)*=(a*b*)*

T=(a+b)*=(a*b*)* so S=T

7,764 views

Can anyone explain in more detail? I am confused that regular expression S will generate more number of b's as compared to expression T. If they need to be equal they both should always generate same set of symbol but number of b's generated by expression S can be more.

Is this solution is an identity of regular expression? or we need to evaluate set of string and make the comparison.

Is this solution is an identity of regular expression? or we need to evaluate set of string and make the comparison.

Search GATE Overflow